2018
DOI: 10.1021/acs.analchem.8b02201
|View full text |Cite
|
Sign up to set email alerts
|

Inertial Microfluidic Syringe Cell Concentrator

Abstract: Low-cost, easy-to-use cell concentration tools are in urgent demand for biomedical diagnosis in resource-poor settings. Herein, we propose a novel inertial microfluidic syringe cell (IMSC) concentrator that employs inertial focusing to increase cell concentration through ordering the cell and removing the cell-free fluid. A three-part structure, consisting of a cap-shaped upper housing, a circular gasket, and a lower housing with a spiral channel, is adopted for simple fabricating and assembling, which enables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 49 publications
0
44
0
Order By: Relevance
“…To better understand the physics of our IM‐centrifuge for cell concentration, we experimentally characterized the particle/cell‐focusing performance in our MFIM chip. The spiral channels in our MFIM chip were designed with simple, two‐loop geometry, and had a low‐aspect‐ratio cross‐section ( AR = channel height ( H )/channel width ( W )) of ∼0.2, according to our previous experiment , which generated a low flow resistance and reduced energy use. The detailed structure parameters of our spiral channels are shown in Supporting Information Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To better understand the physics of our IM‐centrifuge for cell concentration, we experimentally characterized the particle/cell‐focusing performance in our MFIM chip. The spiral channels in our MFIM chip were designed with simple, two‐loop geometry, and had a low‐aspect‐ratio cross‐section ( AR = channel height ( H )/channel width ( W )) of ∼0.2, according to our previous experiment , which generated a low flow resistance and reduced energy use. The detailed structure parameters of our spiral channels are shown in Supporting Information Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our IM‐centrifuge can be employed to concentrate various other bioparticles. The throughput of our IM‐centrifuge is higher than those of other inertial microfluidic concentrators , and is especially suitable for being used under the hand‐powered mode. Further increasing the throughput of our IM‐centrifuge could be realized through multiplexing the cores in the MFIM chip.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a large amount of sheath fluid also significantly increases the operating cost. Other approaches mainly rely on the internally or externally imposed forces, such as inertial,[10] viscoelastic [11], electric [12], acoustic [13], and hybrid forces [14,15]. These approaches can accomplish good separation in many circumstances but may have potential drawbacks when the biological particles are handled.…”
Section: Introductionmentioning
confidence: 99%
“…italicRe0.25em=italicρnormalfitalicUavgitalicDnormalHgoodbreaknormal/italicμ where ρ f is the density of the fluid, D H is the hydraulic diameter of the channel, and µ is the dynamic viscosity of fluid, can reach Re ≈ 400 in comparison with other aforementioned structures, which normally range from 50 to 200 (50 < Re < 200). In the past decade, numerous applications of spiral inertial microfluidics have been shown that can be mainly categorized into separation, e.g., circulating tumor cells (CTCs) enrichment from patient's peripheral blood and concentration or filtration, such as syringe cell concentrator and removal of blood cells for enhancing recovery of viral nucleic acid . Inertial microfluidics throughput is scaled out relatively easily via multiplexing microchannels due to passive focusing of bioparticles, which is dependent only on hydrodynamic forces.…”
Section: Introductionmentioning
confidence: 99%